Antimicrobial activity of grape fruit seed crude extract on microbial growth (Baghdad Science Journal, 2025)
Antimicrobial and antiyeast activity of ethanolic and aqueous extract of grape fruit seed (Citrus paradise ; Rutaceaa) was examined against 10 bacterial and 2 yeast strains. The level of the antimicrobial effects was established using an in vitro agar assay and minimum inhibitory concentration (MIC). In general ethanolic extract were more effective on gram positive bacteria than gram negative bacteria and strongest antimicrobial effect against Streptococcus pyogenes and Salmonella entritidis. Other tested bacteria and yeasts were sensitive to extract ranging from 4 to 16 mg/ml and more.